Diode-pumped 1028 nm Ytterbium-doped fiber laser with near 90% slope efficiency - Harun, Sulaiman Wadi; Paul, M.C.; Moghaddam, M.R.A.; Das, S.; Sen, R.; Dhar, A.; Pal, M.; Bhadra, S.K.; Ahmad, Harith (IOP Publishing, 2010)
Highly efficient laser action from an Ytterbium-doped fiber (YDF) is demonstrated using a fiber Bragg grating (FBG) in conjunction with a 4% Fresnel reflection at room temperature. The YDF used is drawn from Yb2O3-doped preform, fabricated through deposition of porous layer of composition SiO2-GeO2 by the MCVD process in conjunction with a solution doping technique. The fabricated YDF has a core composition of 0.2 wt % of Yb2O3, 1.8 wt % of Al2O3 and 23 wt % of GeO2 with a pump absorption of 9.0 dB/m. The fiber laser operates at wavelength of 1028 nm with a slope efficiency of 88% with respect to the launched 976 nm pump power using the YDF length of 7 m.